Optimized modelling and kinetic analysis of nickel recovery from waste orthodontic implants using response surface methodology. (1st January 2022) - Ans, Muhammad; Atif Makhdoom, Muhammad; Faisal Irfan, Muhammad; Al Abir, Anzum
Highlights: Optimum modelling of nickel leaching using response surface methodology. Optimization of nickel recycling from waste orthodontic – dental alloys. Kinetics controlled model for further verification of parameters. Abstract: With the increasing applications of nickel in industrial homogeneous catalysis, coatings, and batteries a large amount can be recycled from waste orthodontic implants that contain ∼ 10% nickel. This research has reported a cost-effective, low temperature, and environmentally friendly route for recovering nickel from the waste orthodontic implants using a hydrometallurgical technique. Response surface methodology coupled with central composition design (CCD) was employed to optimize and maximize the yield. Leaching time, temperature, rotational speed, and solid–liquid (S-L) ratio were considered independent parameters, while recovery of nickel was taken as a response. A quadratic regression model was developed for the maximization of nickel leaching concerning input parameters and response. Different performance indicators (i.e., RE, RMSE, and MAE) were employed to assess the developed model further. Based on ANOVA analysis, temperature, and S-L ratio were found to be statistically significant factors. The results show a maximum nickel yield of ∼95% was achieved with optimized parameters viz ., temperature (90 °C), leaching time (180 min), rotational speed (40 rpm), and S-L ratio (1:50). Furthermore, the kinetic analysis of the process is also carried out using the Jander rate equation, and the calculated activation energy of nickel leaching with a first-order reaction is 39.8 kJ/mol.